Structural, Raman and optical investigations of barium titanate nanoparticles. (4th March 2022) - Sherlin Vinita, V.; Gowri Shankar Rao, R.; Samuel, J.; Shabna, S.; Joslin Ananth, N.; Shajin Shinu, P. M.; Suresh, S.; Samson, Y.; Biju, C. S.
Abstract: Barium titanate nanoparticles were synthesized via a low temperature sol-gel technique using acetylacetone as a chelating agent. The X-ray diffraction pattern confirmed the formation of tetragonal perovskite structure of the material. The average crystallite size was found to be 49 nm using the Debye-Scherrer method. The Williamson–Hall plot was drawn for evaluating the micro-strain and crystallite size. Raman spectroscopic features typical for the tetragonal phase were identified for Barium titanate powder. In addition to these, an absorption band edge and an optical bandgap were found to be of 406 nm and 3.14 eV respectively. Barium titanate displays polychromatic luminescent peaks in UV -visible regions and it was attributed to the near-band-edge transition and defect states in the optical band gap of the perovskite structure. GRAPHICAL ABSTRACT: UF0001